ANALISIS CHANNEL YOUTUBE SEBAGAI WAKAF PRODUKTIF - Nur Hasan, Ahmad; Hafidhuddin, Didin; Ayuniyyah, Qurroh (Universitas Ibn Khaldun Bogor, 2021)
ABSTRACT Waqf is one of the solutions in the development of Islamic progress. The benefits of waqf are not only felt by the recipients but also benefit the donors as a continues reward (sadaqoh jariyah). the management of waqf into productive waqf is more beneficial for the community because the results of productive waqf will return to the community. the more productive waqf owned by muslim, the better it will be. the result of productive waqf can be use to support the advancement of muslims in various aspects. Therefore, being productive in the digital era, like now, has many forms, including waqf through a youtube channel. building a youtube channel requires creativity, time, energy and thought. A You Tube channel that is donated as waqf must be free from violations of You Tube community guidelines so that it can be easily monetized. after that, the process of transferring to a nadzhir is similar to the handover of waqf of intellectual property. the management of the youtube channel by nadzir must comply with islamic law. the content uploaded is prohibitied from leading to immorality or encouraging sinful behavior. the management of the waqf You Tube channel must also comply with the country’s waqf regulations. the authorized waqf supervisor must be informed of the monthly revenue, operational costs for creating content, and the net profit received for the waqf You Tube channel, which must also adhere to You Tube community guidelines. Keywords: You Tube; analysis of waqf.